PHONOLOGICAL AWARENESS AND PRONUNCIATION DEVELOPMENT AMONG EFL LEARNERS - Daniel Thompson (International Journal of Literature and Language Studies, 2026)
This article investigates the relationship between phonological awareness and pronunciation development among EFL learners within the broader field of linguistics and applied language studies. The study uses pre- and post-task pronunciation recordings from forty intermediate English learners and applies mixed-method pronunciation analysis using teacher ratings, learner reflection notes, and error categorisation. The main finding is that awareness of stress, syllable boundaries, and minimal contrasts improved learners communication clarity more than isolated repetition alone. The article argues that pronunciation teaching should integrate perception, reflection, and communicative practice. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.